1994
DOI: 10.2172/897243
|View full text |Cite
|
Sign up to set email alerts
|

Small geothermal electric systems for remote powering

Abstract: Primary Heat Condenser This report describes conditions and costs at which quite small (100 to 1 ,O00 kilowatt) geothermal systems could be used for off-grid powering at remote locations. This is a first step in a larger process of determining locations and conditions at which markets for such systems could be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…where Revenue = net P × C el and the three later terms are particularly annualized cost of electricity, i.e., investment cost, annual operation and maintenance costs of the overall plant which are assumed to be 4% of the investment cost [31], and well cost. Well cost accounted for the geofluid-pumping and drilling costs, which are arbitrary values dependent on site-specific characteristics.…”
Section: Annual Simulation and Thermo-economic Selectionmentioning
confidence: 99%
“…where Revenue = net P × C el and the three later terms are particularly annualized cost of electricity, i.e., investment cost, annual operation and maintenance costs of the overall plant which are assumed to be 4% of the investment cost [31], and well cost. Well cost accounted for the geofluid-pumping and drilling costs, which are arbitrary values dependent on site-specific characteristics.…”
Section: Annual Simulation and Thermo-economic Selectionmentioning
confidence: 99%
“…A binary plant works with a geothermal resource with temperatures between 190 • C and 260 • C, using a secondary working fluid, usually organic n-pentane with a low boiling point, and a high vapor pressure, governed with low temperatures DiPippo (2016b,a); Entingh et al (1994), as indicated in Figure 2. The plant must operate through a conventional Rankine cycle, that is, the geothermal fluid gives heat to the secondary fluid through heat exchangers, where it is heated and vaporized.…”
Section: Plant Configuration and Efficiencymentioning
confidence: 99%
“…Main cost categories included in this model are briefly explained below, in accordance with Entingh et al (1994):…”
Section: Geothermal Balance Of Systemmentioning
confidence: 99%
“…On the contrary, that is the inner diameter being nearly as large as the pipe outer diameter, the flow will be hindered by the narrowness of the annular space [22,28]. In both cases, the total pressure drop to be overcome by the pump is extremely excessive.…”
Section: Optimum Diameter Ratiomentioning
confidence: 99%